(untitled) (Journal of Geography and Environmental Management, 2024)
On the territory of the West Kazakhstan region there are recognized environmental disaster zones and provinces with dangerous levels of chemical or radiation contamination. The goal is to monitor the environmental condition of the territory of the West Kazakhstan region as a result of industrial activities. Carrying out research work will contribute to the sustainable development of the West Kazakhstan region by improving soil quality, improving environmental safety and protecting public health. The measures taken will help preserve the region’s land resources and ensure the well-being of its residents on a long-term basis. The comparative analytical method will allow us to establish the features of the formation and migration of soil fauna along the soil profile in conjunction with changes in other soil properties. A comprehensive database has been created on morphological, chemical, physical and physicochemical properties, as well as on possible sources of pollution. Methodological foundations for assessing soil contamination by toxic chemicals have been developed. Comprehensive studies are being carried out on the ecological state of the soil cover of the West Kazakhstan region. The following are being developed: an information database and methodological basis for assessing soil pollution by toxic chemicals; recommendations for preventing pollution by toxic chemicals to improve the environmental situation in the region.